All the men I've loved again : a novel - Pride, Christine (Atria Books, 2025)
"From Christine Pride, the beloved coauthor of the Good Morning America Book Club Pick We Are Not Like Them, comes a dazzling solo debut novel about a woman who finds herself in a love triangle with two men in her early twenties, and then again, in her forties. It's 1999, TLC's "No Scrubs" is topping the charts, y2k is looming on everyone's mind, and Cora Belle has arrived at college ready to change her life. She's determined to grow out of the shy, sheltered girl who attended an all-white prep in her all-white suburb. Cora is ready to conquer her fears and find her people, her place in the world, and herself. What she's totally unprepared for is Lincoln, with his dark skin, charming southern drawl, and that smile. Because how can you ever prepare yourself for the rollercoaster of first love with all its glorious, bewildering contradictions? Just when Cora thinks she's got things figured out, a series of surprises and secrets threaten to upend everything she thought she understood about love and loyalty. In the wake of these developments and a shocking tragedy, a new man enters Cora's life-Aaron-further complicating everything. He's the only one who seems to get her, and the letters she writes to him when the two are separated reveal the truth of their inescapable connection. There's only one problem-how can she fall in love with one man when her heart belongs to another? Twenty years later, and Cora is all grown up, or mostly, and has cloaked herself in loneliness like a warm blanket. It's the safest choice. But then an unexpected reconnection and a chance encounter puts her right back where she started. The same two men, the same agonizing decision. Finding herself in this position-again-will test everything Cora thought she knew about fate, love, and most importantly, herself. All The Men I've Loved Again is a big-hearted coming-of-age story for anyone who's thought what if about a past love and what it would be like to have a second chance"--